Smart responsive in situ hydrogel systems applied in bone tissue engineering - Wu, Shunli; Gai, Tingting; Chen, Jie; Chen, Xiguang; Chen, Weikai (Frontiers in Bioengineering and Biotechnology, 2024)
The repair of irregular bone tissue is still suffering severe clinical problems, due to scarcity of the appropriate therapeutic carrier to match the dynamic and complex bone damage. Fortunately, the stimuli-responsive in-situ hydrogel systems, which are triggered by special microenvironment, pave an ideal way to regenerate bone tissue, because of possessing the injectability, in-situ gelatin and spatiotemporally tunable releasing drugs. Herein, we introduce the two main stimulus-response approaches (exogenous stimulus-response and endogenous stimulus-response) to form in-situ hydrogels in bone tissue engineering. Firstly, we summarized specific and distinct responses to an extensively range of external stimuli (e.g., Ultraviolet, Near Infrared, Ultrasound, etc.) to in-situ form hydrogels, which modified biocompatible materials by various functional groups or hybrid functional nanoparticles. Furthermore, “Smart” hydrogels, which is respond to endogenous physiological environmental stimulus (e.g., Temperature, pH, Enzyme, etc.), can achieve the in-situ gelation by once injection in vivo without extra work. Moreover, the mild chemistry respond mediated in-situ hydrogel systems also playing fascinating prospects in bone tissue engineering, such as Diesel-Alder reaction, Michael addition reaction, Thiol-Michael addition reaction, and Schiff, etc. The recent developments and challenges of various “Smart” in-situ hydrogels and their application to drug administration and bone tissue engineering is concerned in this review. It is anticipated that advanced strategies and innovative ideas of in-situ hydrogels will be exploited in the clinical field and increase the life quality of bone damage patients.